(untitled) (Proceedings of Scientific Conference on Multidisciplinary Studies, 2024)
This paper explores the evolution of writing instruction within language education, tracing its development from traditional methods to contemporary practices. Initially, language instruction focused predominantly on grammar and rote memorization, but over time, pedagogical shifts have emphasized communicative competence and process-oriented approaches. This study examines key milestones in writing instruction, including the influence of cognitive and sociocultural theories, the integration of technology, and the adoption of genre-based and collaborative learning strategies. By analyzing historical and current methodologies, this paper aims to highlight effective practices and identify ongoing challenges in teaching writing. The findings suggest that while significant progress has been made, educators must continually adapt to emerging trends and diverse learner needs to enhance writing instruction in language education.